2019
DOI: 10.4049/jimmunol.1800618
|View full text |Cite
|
Sign up to set email alerts
|

TLR-Induced IL-12 and CCL2 Production by Myeloid Cells Is Dependent on Adenosine A3 Receptor–Mediated Signaling

Abstract: TLR-induced signaling potently activates cells of the innate immune system and is subject to regulation at different levels. Inflammatory conditions are associated with increased levels of extracellular adenosine, which can modulate TLR-induced production of cytokines through adenosine receptor–mediated signaling. There are four adenosine receptor subtypes that induce different signaling cascades. In this study, we demonstrate a pivotal contribution of adenosine A3 receptor (A3R)–mediated signaling to the TLR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…NAMPT, the rate-limiting enzyme in the salvage pathway, is up-regulated by several different viruses, including HIV and Zika virus [ 147 , 148 ]. Searching publicly available microarray and next-generation sequencing data revealed that NAMPT transcription is significantly up-regulated during many immune-related processes, such as myeloid differentiation [ 149 ], lipopolysaccharide (LPS) treatment [ 150 , 151 ], and T cell activation [ 152 ]. This transcriptional data is consistent with the idea that under infections, NAD + biosynthesis needs to be increased.…”
Section: The Regulation Of Nad + Biosynthesis During Infectionsmentioning
confidence: 99%
“…NAMPT, the rate-limiting enzyme in the salvage pathway, is up-regulated by several different viruses, including HIV and Zika virus [ 147 , 148 ]. Searching publicly available microarray and next-generation sequencing data revealed that NAMPT transcription is significantly up-regulated during many immune-related processes, such as myeloid differentiation [ 149 ], lipopolysaccharide (LPS) treatment [ 150 , 151 ], and T cell activation [ 152 ]. This transcriptional data is consistent with the idea that under infections, NAD + biosynthesis needs to be increased.…”
Section: The Regulation Of Nad + Biosynthesis During Infectionsmentioning
confidence: 99%
“…The role of this receptor in the pathophysiology of inflammation is complex. Putten et al [60] pointed out that A3R-mediated signaling induced proinflammatory cytokines, while another study showed the protective effect of preventing excessive immune response and immune-mediated damage after A3R activation [61]. To date, research on downregulated ADORA3 and IPAH pathogenesis is insufficient, and the underlying mechanisms still need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In immature human dendritic cells adenosine can stimulate A1 and A3 receptor to increase Ca ++ mobilization and actin polymerization, which were associated with increased chemotaxis [52]. Stimulation of A3 receptors in the presence of various inflammatory stimuli through different TLR receptors or in the presence of whole pathogens also promotes IL-12 secretion [53]. A3 signaling was also important for DC-mediated polarization of T cells into Th1 or Th17 phenotypes [53].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Stimulation of A3 receptors in the presence of various inflammatory stimuli through different TLR receptors or in the presence of whole pathogens also promotes IL-12 secretion [53]. A3 signaling was also important for DC-mediated polarization of T cells into Th1 or Th17 phenotypes [53]. In mature human or mouse dendritic cells; however, adenosine signaling suppresses IL-12 production [54,55].…”
Section: Dendritic Cellsmentioning
confidence: 99%